Left Ventricular Noncompaction Cardiomyopathy (LVNC): A Case Report - Ahmed, Tofayel Uddin; Haque, Amdadul; Khan, Parvez Rahman (Community Based Medical Journal, 2022)
Left ventricular noncompaction is a rare congenital cardiomyopathy. It can occur in isolation or coexist with other cardiac anomalies. Clinical presentation varies from patients to patients. LVNC is commonly diagnosed by echocardiography. We descried the case of a man with heart failure for the first time at 55 years of age. Transthoracic echocardiography shows trabeculation and intertrabecular recesses communicate with the ventricle cavity. The patient was relatively well after medical management. This case is reported for clinical awareness and share experience. CBMJ 2022 July: vol. 11 no. 02 P: 162-166